2022
DOI: 10.3389/fimmu.2022.966184
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and genetic evidence for the impact of CD5 and CD6 expression and variation in inflammatory bowel disease

Abstract: Crohn’s disease (CD) and ulcerative colitis (UC) are inflammatory bowel diseases (IBD) resulting from the interaction of multiple environmental, genetic and immunological factors. CD5 and CD6 are paralogs encoding lymphocyte co-receptors involved in fine-tuning intracellular signals delivered upon antigen-specific recognition, microbial pattern recognition and cell adhesion. While CD5 and CD6 expression and variation is known to influence some immune-mediated inflammatory disorders, their role in IBD remains u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…CD6 is predominantly expressed by peripheral T lymphocytes, myeloid thymocytes, and B1a lymphocytes, constituting a type I transmembrane glycoprotein. It exerted an inhibitory effect on T-cell activation while also promoting colonic inflammatory responses [51,52]. Knockout of TAP1 in mice led to the activation of their natural cell-killing capacity [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…CD6 is predominantly expressed by peripheral T lymphocytes, myeloid thymocytes, and B1a lymphocytes, constituting a type I transmembrane glycoprotein. It exerted an inhibitory effect on T-cell activation while also promoting colonic inflammatory responses [51,52]. Knockout of TAP1 in mice led to the activation of their natural cell-killing capacity [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…SRCR domains are divided into Group A and Group B based on the number and position of conserved cysteine residues [16,17], with Group A having six cysteine residues that form three pairs of disulfide bonds, and Group B having eight cysteine residues that form four pairs of disulfide bonds [18]. For instance, CD5 (cluster of differentiation 5) [19], CD6 (cluster of differentiation 6) [20], and DMBT1 (deleted in malignant brain tumor 1) [21] belong to Group B, whereas MARCO (macrophage receptor with collagenous structure) [22], Mac2BP (Mac-2 binding protein) [23], and LOX (lysyl oxidase) family (LOX-like 2, LOX-like 3, and LOX-like 4) [24] belong to Group A. Until now, research on SRCR-SFs within Group B has primarily focused on vertebrates, with only one reported instance in the invertebrate Geodia cydonium [25].…”
Section: Introductionmentioning
confidence: 99%